Types of Variantivity in the Polish Language - Ruszkovski, Marek (Respectus Philologicus, 2014)
The occurrence of linguistic variants is called variantivity (in Polish: wariantywność) or variance (in Polish: wariancja). Not always does the term linguistic variance have an identical meaning. In this paper, it is understood in its narrower meaning, i.e., it encompasses linguistic elements that differ in form but have the same or a similar function. It deals with both variants sensu stricto (i.e., identical as far as the function is concerned) and oscillating variants (i.e., those that differ from one another in one quality). Linguistic variantivity can be classified using the following criteria: 1. Linguistic correctness (correct and incorrect alternate forms); 2. Area of linguistic operation: extralinguistic (spelling and punctuation) and intralinguistic (grammar, lexis, phonetics); 3. Universality of usage (systemic and idiolectic variants); 4. Frequency (frequent and rare forms); 5. Chronology (contemporary and outdated forms); 6. Geography (countrywide and regional variants); 7. Range (countrywide and noncountrywide forms characteristic of a particular milieu, profession, etc.); and 8. Stylistics (neutral and marked forms). The typology presented in this paper is open, which means that other criteria can be added to discriminate alternate forms (for instance, the criterion of genetics—native and non-native variants). Some criteria overlap, e.g., outdated, regional, idiolectic, environmental, and/or stylistically marked forms can all be considered rare (the criterion of frequency). Putting that aside, this classification can be expected to contribute to a better recognition of the phenomenon of variantivity in the Polish language.